Cutaneous involvement in multiple myeloma: a multi-institutional retrospective study of 53 patients. Issue 9 (1st September 2016) - Jurczyszyn, Artur; Olszewska-Szopa, Magdalena; Hungria, Vania; Crusoe, Edvan; Pika, Tomas; Delforge, Michel; Leleu, Xavier; Rasche, Leo; Nooka, Ajay K.; Druzd-Sitek, Agnieszka; Walewski, Jan; Davila, Julio; et al.
Abstract: Skin infiltration in multiple myeloma (skin MM) is a rare clinical problem. Only a few cases of skin involvement have been reported, primarily in single case reports. We analyzed and present the clinical outcomes, immunohistochemistry and cytogenetic features, and relevant laboratory data on 53 biopsy-proven skin MM cases. The median time from MM diagnosis to skin involvement was 2 years. There appears to be an overrepresentation of immunoglobulin class A (IgA) and light chain disease in skin MM. We found no correlation between CD56 negative MM and skin infiltration. We found that skin MM patients presented in all MM stages (i.e. ISS stages I to III), and there was no preferential cytogenetic abnormality. Patients with skin MM carry a very poor prognosis with a median overall survival (OS) of 8.5 months as time from skin involvement. Moreover, patients with IgA disease and plasmablastic morphology appear to have a worse OS.